Осторожно, работает десантура! - Зверев Сергей Иванович (Спецназ, 2016)
Экземпляры: аб. ЦБ (2018.14.03) / Инвентарный номер: 4170 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44